2007
DOI: 10.1111/j.1365-2702.2006.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Chinese nurses’ current knowledge of pain in older people

Abstract: The findings in this survey highlight a significant pain management knowledge deficit among the nurses in the clinical practice. The findings may help the nurses realize their knowledge deficit in this area and may also suggest curriculum changes for the nurses to improve pain management knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
2
9
0
1
Order By: Relevance
“…This study found a knowledge deficit among respondents, as shown by an overall mean total score of 65%. This finding is comparable with the results of studies in other countries in which the same survey instrument was used, where average scores were 41% (Yu and Petrini 2007) and 71% (Sloman et al 2001). Unlike other instruments (McCaffery and Robinson 2002), the Pain in the Elderly Questionnaire has no minimum acceptable score, but it is concerning that more than one third (n=35) of respondents in this study scored no more than 57%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study found a knowledge deficit among respondents, as shown by an overall mean total score of 65%. This finding is comparable with the results of studies in other countries in which the same survey instrument was used, where average scores were 41% (Yu and Petrini 2007) and 71% (Sloman et al 2001). Unlike other instruments (McCaffery and Robinson 2002), the Pain in the Elderly Questionnaire has no minimum acceptable score, but it is concerning that more than one third (n=35) of respondents in this study scored no more than 57%.…”
Section: Discussionsupporting
confidence: 87%
“…The entire questionnaire or parts of it have been used in other studies (Yu andPetrini 2007, Gregory andHaigh 2008). A higher score on the questionnaire indicates greater knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…This may be linked to the infrequency of continuing education; all but one of these 24.8% respondents had attended one session in continuing education while the remaining respondent had attended two sessions. Education in pain management is not mandatory for continuing professional accreditation in China , so it is encouraging to see that a proportion of people in our survey participate in continuing education and are sufficiently motivated to travel for the purposes of participation in education. It is also encouraging that Chinese hospitals are prepared to provide financial support for nurses to attend continuing education in pain assessment.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons was that many of them missed specific pain assessment even though the standardized patients portrayed a patient with chest pain. In general, the level of pain intolerance in Eastern cultures may be higher than that in Western Yu and Petrini (2007) reported a significant deficit in knowledge of pain among Chinese nurses.…”
Section: Discussionmentioning
confidence: 90%
“…In general, the level of pain intolerance in Eastern cultures may be higher than that in Western cultures, which may result in less attention to pain management in nursing curricula in the IEN's original home countries with Eastern cultures. For instance, Yu and Petrini () reported a significant deficit in knowledge of pain among Chinese nurses.…”
Section: Discussionmentioning
confidence: 99%